2016
DOI: 10.1111/1556-4029.13059
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Voltammetric Analysis of Δ9THC for the Reduction of False Positive Results in the Analysis of Suspected Marijuana Plant Matter

Abstract: The development of methodologies using inexpensive, fast, and reliable instrumention is desirable in illicit drug analysis. The purpose of this study was based on cyclic voltammetry technique to differentiate the electrochemical behavior of ∆(9) -THC, the psychoactive substance in marijuana, and five different extract plants to yield false positive results after analysis protocol for cannabinoids using thin-layer chromatography and Fast Blue B salt. After applying a deposition potential of -0.5 V in a glassy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The literature involving voltammetric determination of Δ9-THC comprehends the use of electrodes with and without chemical modification. There are methodologies for its detection when in seized samples [26][27][28][29][30] , and in saliva 31,32 . However, it should be noted that in the literature only a few studies with artificial saliva have been reported for the electrochemical detection of Δ9-THC 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The literature involving voltammetric determination of Δ9-THC comprehends the use of electrodes with and without chemical modification. There are methodologies for its detection when in seized samples [26][27][28][29][30] , and in saliva 31,32 . However, it should be noted that in the literature only a few studies with artificial saliva have been reported for the electrochemical detection of Δ9-THC 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical sensors can be classified based on the type of electrochemical transducer employed. Voltammetry is the most widely used transduction event for the rapid quantitative sensing of illicit drugs with studies performed on NBOMes in blotter samples (Oiye et al, 2017), cocaine residue (Tavakkoli et al, 2019), and Δ 9 ‐tetrahydrocannabinol in plant matter (Balbino et al, 2016). Highly sensitive amperometric detection of morphine has used a modified screen‐printed electrode (Maccaferri et al, 2019), while the sensitive impedimetric detection of cocaine using molecularly imprinted polymer nanoparticle receptors showed no cross reactivity with morphine (D'Aurelio et al, 2020).…”
Section: Sensorsmentioning
confidence: 99%
“…The glassy carbon electrode was found superior due to a lower LOD in comparison to the platinum working electrode (6.2 x 10 -10 vs 2.7 x 10 -8 for the glassy carbon and platinum electrode, respectively). Later Balbino et al (2016) published a CV-method using the same type of glassy carbon electrode for the detection of Δ9-THC in suspected marijuana plants. The same accumulation time of 30 s was kept.…”
Section: Voltammetric Sensorsmentioning
confidence: 99%